Systematic Literature Review: Efektivitas Pembelajaran Mendalam Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Menegah Atas - Hubaib, Ilhamurrahman M; Triana, Siti Hardiyanti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the effectiveness of deep learning in enhancing the critical thinking skills of high school (SMA) students. A systematic literature review was conducted by searching for articles on Google Scholar using the "Publish or Perish" application, covering the period from 2020 to 2025. This process yielded eight articles meeting the inclusion criteria for in-depth analysis. The findings indicate that deep learning is effective in improving high school students’ critical thinking skills within specific subject contexts; however, successful implementation also depends on teacher competence, institutional support, the availability of digital facilities, and student readiness to adapt to new or deep learning approaches. Nevertheless, significant implementation gaps remain in the field, particularly regarding students’ digital literacy skills. This study aims to provide evidence-based recommendations for educators and policymakers to optimize the implementation of the Ministry of Basic and Secondary Education Regulation Permendikdasmen Number 13 of 2025 concerning deep learning across all levels of basic and secondary education in Indonesia.